Ammonia removal from mixed dewatering liquors by three different deammonification technologies. Issue 12 (10th November 2020) - Ochs, Pascal; Martin, Benjamin D.; Germain, Eve; Stephenson, Tom; van Loosdrecht, Mark C. M.; Soares, Ana
Abstract : Deammonification is an established biological nitrogen removal process for dewatering liquors from anaerobic digestion. Abstract : Deammonification is an established biological nitrogen removal process for dewatering liquors from anaerobic digestion. Different deammonification technologies are being commercialised varying in control philosophy, biomass structure and reactor design. In this study three different pilot scale deammonification technologies were investigated to assess total nitrogen removal from mixed (pre and post digestion) dewatering liquors originated from thermal hydrolysis based anaerobic digestion process. The technologies tested included a suspended sludge sequencing batch reactor (S-SBR), a moving bed biofilm reactor (MEDIA) and a granular sludge sequencing batch reactor (G-SBR). This is the first study to compare side-by-side, three different deammonification technologies. All tested technologies were operated according to the manufacturer guidelines and demonstrated suitable nitrogen removal at loads varying between 0.3–0.8 kgN m −3 d −1 . During the operation of three technologies, periods of poor effluent quality due to disruptions or imbalances in the biological reactions were observed. The S-SBR had the lowest number of imbalances with 14 cases relating to free nitrous acid inhibition. Both S-SBR and MEDIA presented the highest nitrogen removal rate with 0.72 and 0.68 kgN m −3 d −1, respectively. The G-SBR achieved nitrogen removal rates of 0.31 kgN m −3 d −1 while presenting the highest number of imbalances that were related to inhibitive concentration of free ammonia or free nitrous acid of anammox. These inhibitions were caused by the control system relying on surrogate measurements for ammonia. Finally, only the S-SBR was operated at temperatures below 20 °C, caused by seasonal fluctuations, but still achieved nitrogen removal rates of 0.30 kgN m −3 d −1 . The number of deammonification technologies is growing, however, only a few but contradictive comparison studies exist. This comparison study can provide support for selection of sidestream deammonification technologies, by identifying the critical parameters.